Movability of morphisms in an enrichedpro-category and in a J-shape category - Gevorgyan, P. S.; Pop, I. (Հայաստանի ԳԱԱ)
Various types of movability for abstract classical pro-morphisms or coherent mappings, and for abstract classical or strong shape morphisms was given by the same authors in some previous paper [10], [11], [12]. In the present paper we introduce and study the notions of (uniform) movability, and (uniform) co-movability for a new type of pro-morphisms and shape morphisms belonging to the so called enriched pro-category proJ -C and to the corresponding shape category ShJ (C,D), which were introduced by N. Ugleˇsi´c [27].
Keywords: Mathematics